2002
DOI: 10.1080/00222890209601953
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transfer Benefits of Increased Practice for Constant, Blocked, and Serial Practice Schedules

Abstract: The effects of practice schedule and amount of practice on the development of the generalized motor program (GMP) and on parameter estimation were investigated. Participants (N = 108) practiced the same relative timing but different absolute durations of a multisegment timing task. Practice schedules (constant, blocked, or serial) were crossed with amounts of practice (low and high). Inclusion of a constant practice condition allowed the authors to investigate the variability of practice prediction. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
2
35
0
4
Order By: Relevance
“…When the transfer test consists of performing a task with the same relative timing structure (same GMP) practiced in the acquisition phase, but with a new value of absolute timing, a lower amount of constant practice produces less relative timing errors than a higher amount of constant practice (Giuffrida,Shea,Fairbrother 13 , see post-test 2). On the other hand, Giuffrida, Shea, Fairbrother 13 did not find an amount of practice effect on absolute timing errors. Using the schema theory concept 1 , the amount of practice affected the GMP, but not the parameterization.…”
Section: Constant Practicementioning
confidence: 93%
See 4 more Smart Citations
“…When the transfer test consists of performing a task with the same relative timing structure (same GMP) practiced in the acquisition phase, but with a new value of absolute timing, a lower amount of constant practice produces less relative timing errors than a higher amount of constant practice (Giuffrida,Shea,Fairbrother 13 , see post-test 2). On the other hand, Giuffrida, Shea, Fairbrother 13 did not find an amount of practice effect on absolute timing errors. Using the schema theory concept 1 , the amount of practice affected the GMP, but not the parameterization.…”
Section: Constant Practicementioning
confidence: 93%
“…Using the schema theory concept 1 , the amount of practice affected the GMP, but not the parameterization. A possible explanation for this interaction between the amount of practice and constant practice is that the relative and absolute dimensions were consolidated, in the course of acquisition, into a single unit that was unavailable for updating 13 . Studies using new paradigms of investigation have also shown that transfer depends on type and amount of practice experienced 26,27 .…”
Section: Constant Practicementioning
confidence: 99%
See 3 more Smart Citations